Epidemiology of enterotoxigenic Escherichia coli among children under five years in Kenya’s urban informal settlement - Njuguna, Amos; Maingi, John M.; Mbae, Cecilia; Otieno, Phelgona; Kering, Kelvin; Mbithi, Winfred; Kioko, Christine; Osman, Rahma; Kibet, Evans; Kariuki, Samuel (Frontiers in Microbiology, 2025)
IntroductionEnterotoxigenic Escherichia coli (ETEC) is a significant cause of diarrheal morbidity and mortality among children under 5 years, particularly in low and middle-income countries. This study aimed to determine the prevalence of ETEC and associated risk factors among children under five presenting with diarrhea in health facilities in Mukuru slums of Nairobi, Kenya, where poor sanitation and hygiene practices are prevalent.MethodsUsing a cross-sectional design, we recruited 387 children under five years of age with acute diarrhea. Total nucleic acid (TNA) was extracted from stool samples and analyzed using a PCR-based customized TaqMan Array Card (TAC), which included three ETEC toxin genes (LT, STh, and STp) and six ETEC colonization factors (CFs). A structured questionnaire was employed to collect participants information.FindingsETEC was detected in 148/387 samples, yielding a prevalence of 38.2% (95% CI: 34.2–42.2%). Both heat-labile and heat-stable (LT/ST) enterotoxin genes were the most common (43%) followed by heat-labile (30%), and heat-stable (27%). Colonization factors (CF) were present in 52% (77/148) of ETEC-positive samples with CS6 being the most frequently detected CF at 36.3% (28/77). Children aged 13–24 months had significantly elevated odds of infection (aOR = 2.48; 95% CI: 1.36–4.52, p = 0.003), as well as those aged 25–36 month (aOR = 2.12; 95% CI: 1.10–4.10, p = 0.025), 37–48 months (aOR = 2.45; 95% CI: 1.21–4.97, p = 0.013), and 49–59 months (aOR = 2.59; 95% CI: 1.12–6.01, p = 0.027). Households lacking access to private flush toilets exhibited a tripled risk (aOR = 3.04; 95% CI: 1.38–6.71, p = 0.006) of ETEC positivity.ConclusionThese findings highlight the urgent need for targeted public health interventions, including improved sanitation and hygiene practices and vaccine introduction, to mitigate the burden of ETEC-related diarrhea among high-risk populations in disease endemic settings.